Analisis Faktor Penyebab Ketidaklengkapan Pengisian Resume Medis Rawat Inap Di RSU Bahagia Makassar - Zahratul Jannah AT Tabrani; Sabran Sabran; Dony Setiawan Hendyca Putra; Gamasiano Alfiansyah (ARTERI : Jurnal Ilmu Kesehatan, 2025)
Incomplete medical resume documentation remains a persistent issue, including at Bahagia General Hospital Makassar. In the Cempaka inpatient ward, the percentage of incomplete medical resumes in November, December, and January reached an average of 8.00 and showed an increasing trend. This study aims to analyze the factors contributing to the incompleteness of medical resume documentation based on Armstrong and Baron’s (1998) performance theory. The study employed a qualitative approach through interviews, observations, documentation review, and brainstorming. Research subjects consisted of physicians, nurses, and medical record staff. The findings indicate several contributing factors. Individual factors include the suitability of staff educational backgrounds, the absence of training related to medical resume completion, and limited knowledge regarding completeness standards (SPM). Leadership factors involve the lack of motivational strategies such as rewards for staff who consistently complete medical resumes, as well as insufficient involvement of all staff in completeness evaluations. System factors include suboptimal use of checklist forms, the absence of standardized operating procedures (SOP) for completing and assessing medical resumes, and the lack of SOP socialization. Situational factors are related to workload issues, particularly staff performing multiple roles (double jobs). Meanwhile, group factors were found to function well through effective teamwork among staff. In conclusion, incompleteness in medical resume documentation is influenced by individual, leadership, system, and situational factors. It is recommended to provide training for involved staff, develop and implement SOPs, and conduct SOP socialization to improve medical resume completeness.